1996
DOI: 10.1137/s0363012993253534
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical System Approach to Stochastic Approximations

Abstract: It is known that some problems of almost sure convergence for stochastic approximation processes can be analyzed via an ordinary differential equation (ODE) obtained by suitable averaging. The goal of this paper is to show that the asymptotic behavior of such a process can be related to the asymptotic behavior of the ODE without any particular assumption concerning the dynamics of this ODE. The main results are as follows: a) The limit sets of trajectory solutions to the stochastic approximation recursion are,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
270
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(277 citation statements)
references
References 23 publications
4
270
0
3
Order By: Relevance
“…As the piecewise linear interpolation of sequence {θ n } n≥0 falls into the category of such solutions, the concept of chain-recurrence is tightly connected to the asymptotic behavior of stochastic gradient search. In [5], [6], it has been shown that for unbiased gradient estimates, all limit points of {θ n } n≥0 belong to R and that each element of R can potentially be a limit point of {θ n } n≥0 with a non-zero probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the piecewise linear interpolation of sequence {θ n } n≥0 falls into the category of such solutions, the concept of chain-recurrence is tightly connected to the asymptotic behavior of stochastic gradient search. In [5], [6], it has been shown that for unbiased gradient estimates, all limit points of {θ n } n≥0 belong to R and that each element of R can potentially be a limit point of {θ n } n≥0 with a non-zero probability.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in general, a limit point of {θ n } n≥0 is in R but not necessarily in S. For more details on chain-recurrence, see [5], [6], [14] and references therein. Given these results, it will prove useful to involve both R and S in the asymptotic analysis of biased stochastic gradient search.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we study the limiting behavior, as the number of steps grows, of the proportion of balls in the bins of G. More specifically, let N 0 = m i=1 B i (0) denote the initial total number of balls, let 2) be the proportion of balls at vertex i after step n, and let x(n) = (x 1 (n), . .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…6 Motivation for such an 3 The subsequent arguments can accommodate an infinite measure space S together with the Hilbert space Y = L 2 (S, E) of square-integrable profiles s 7 → y s ∈ E, mapping S into a Euclidean space E. 4 That state-contingent claim could quite simply come as a financial credit or debit. Then E = R. Alternatively, if real assets generate various goods, mentioned on a finite list G, then E = R G .…”
Section: Cooperative Risk Sharingmentioning
confidence: 99%
“…Since the latter converges, so does the bilateral process by Prop. 2.1 in [3]. ¤ It deserves emphasis that players may very well be scantly informed.…”
Section: Given Now Ymentioning
confidence: 99%